1990
DOI: 10.1111/j.1095-8649.1990.tb05631.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial involvement in ulcerative condition of air‐breathing fish from India

Abstract: Four types of bacteria, two fluorescent pseudomonads, one aeromonad (Aeromonas hydrophila anaerogens) and one coccus (Micrococcus varians) were isolated from skin lesions of airbreathing fishes. The bacterial culture in mixed condition induced severe ulcers in healthy Anabas testudineus. Pure cultures of each of two pseudomonads and an aeromonad separated from the mixture induced superficial ulcer formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Roberts et al (1989) carried out a survey of the ulcerative disease in Bangladesh where A. hydrophila and A. sobria were found to be the dominant bacteria in the EUS lesions and ulcers. Pal and Pradhan (1990) carried out a study on the bacterial involvement in ulcerative condition of air-breathing catfish in India and isolated four types of bacteria, two of which were fluorescent pseudomonads, one aeromonad (A. hydrophila) and one coccus (Micrococcus varians) from skin lesions of the fish. Chowdhury et al (2002) observed the severity of the ulcerative disease in different fishes with concurrent infection of Aphanomyces invadans and Aeromonas bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al (1989) carried out a survey of the ulcerative disease in Bangladesh where A. hydrophila and A. sobria were found to be the dominant bacteria in the EUS lesions and ulcers. Pal and Pradhan (1990) carried out a study on the bacterial involvement in ulcerative condition of air-breathing catfish in India and isolated four types of bacteria, two of which were fluorescent pseudomonads, one aeromonad (A. hydrophila) and one coccus (Micrococcus varians) from skin lesions of the fish. Chowdhury et al (2002) observed the severity of the ulcerative disease in different fishes with concurrent infection of Aphanomyces invadans and Aeromonas bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…And also the present investigation deals with the comparison of blood parameters with special reference to the microbial flora of fresh water fish of Channa punctatus infected and control fish. In the EUS affected murrels captured from the wild, different pathogenic organisms including Fungi, A. invadans, (Chinabut 1995), bacteria A. hydrophila, Vibrio sp., (Pal and Pradhan 1990) and Virus (Frerichs 1995) have been detected. Among the fish potential pathogens were identified, Aeromonas and pseudomonas species pose the most significant threats to murrel fishes.…”
Section: Resultsmentioning
confidence: 96%
“…Aeromonas hydrophila is also found with this fungi (Karunasagar et al 1995). These pathogens seize the blood circulation and resulting edema of the abdominal cavity (Pal and Pradhan 1990). The epithelial layer of the skin, gills and alimentary tract, confer potential sites for these pathogens (Gobinath and Ravichandran 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fish it was reported to be the causative agent for ulcerative disease syndrome (UDS) [2] although the pathogenesis of A. hydrophila induced UDS is not well understood [3].…”
Section: Introductionmentioning
confidence: 99%